PENYELESAIAAN PERKARA PIDANA MELALUI MEDIASI PENAL TERHADAP TINDAK PIDANA PENGANIAYAAN PADA MASYARAKAT ADAT DESA KUBU BALING-BALING KECAMATAN TAMBUSAI KABUPATEN ROKAN HULU - Al Qudri; Evi Deliana; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Penal mediation is the settlement of cases outside the court, in Indonesia the settlement of cases outside the court or Alternative Dispute Resolution (ADR) is only known in the civil sphere, whereas for the criminal sphere the settlement is reached by proceeding through the court. The practice of settling criminal cases outside the cour,t so far has no formal legal basis, so there is often an informal case where there has been a peaceful settlement even though through the mechanism of traditional law, it is still processed in court according to national law.This type of research can be classified in the type of sociological (empirical) legal research, because in this study the authors directly conduct research at the location or place of study in order to provide a complete and clear picture of the problem under study. This research was conducted in the Central Tambusai region, Tambusai District, Rokan Hulu Regency. While the population and sample are Datuk Luhak Tambusai Customary Institution, Ninik Mamak Density of Luhak Tambusai Adat, Chief of Tambusai Luhak Sector Police and Perpetrators and Victims of Abuse in Luhak Tambusai Village.The conclusions that can be obtained from the results of the study are: First, the completion of criminal cases through Penal Mediation against criminal acts of persecution in the indigenous community of Kubu Baling Baling Village, Tambusai District, Rokan Hulu Regency, has not been implemented well. This is proven that, the perpetrators are still not fully with mamak ninik. The parties are still inclined to take the case to the litigation channel. The parties should be able to appreciate the existence of ninik mamak in settling criminal cases through Penal Mediation for criminal acts of persecution in the Kubu Baling Baling Indigenous Village community. The people around still don't realize the existence of customary law as an alternative in resolving cases that occur in the community. Second, the efforts to resolve criminal cases through mediation of penalties in order to reduce the occurrence of criminal acts of persecution in the indigenous communities of Kubu Baling Desa Tambusai District, Rokan Hulu Regency, among others, strengthening and empowering the role of ninik mamak, increasing cooperation with law enforcement officials, and empowering institutions custom.Keywords: Settlement, Criminal Case, Penal Mediation, Indigenous Peoples